Back to the future: radiosurgery in the new frontier - Vermuelen, Sandra; Murphy, Kevin T.; Giap, Huan (Translational Cancer Research, 2014)
From its inception more than sixty years ago by pioneer neurosurgeon, Dr. Lars Leksell (1907-1986), stereotactic radiosurgery (SRS) has been a radical departure from conventional fractionated radiation treatment, drawing a large number of doubters. Just the thought of applying a very large dose of radiation to a critical organ such as the brain brought back the bad memories of radiation treatment in its early days a century ago.